Training effect of special basketball exercises - Koryahin, V.; Blavt, O.; Doroshenko, E. Yu.; Prystynskyi, V.; Stadnyk, V.; Дорошенко, Едуард Юрійович (My University, 2020)
The study objective is to evaluate the immediate training effect under the influence of changes in the parameters of physical activity in special exercises on the basis of physiological changes in the body of basketball players.Materials and methods. The study used empirical methods of measuring heart rate during competitions, pulmonary ventilation values, О2 consumption during physical work, О2-debt, “excess” CО2, methods of mathematical statistics. Results. An empirical study has shown that the exercises used in the preparation of basketball players differ significantly in the nature of physiological action. The greatest physiological shifts in the body of basketball players determine the exercise, which is performed intensively or repeatedly with maximum intensity. The smallest physiological shifts were found when performing free throws. Conclusions. The magnitude and orientation of the immediate training effect of special exercises in basketball depend on the combination of the effects of all the main indicators of physical activity – the type of exercises used, their intensity and duration, duration of rest, the number of repetitions.
Keywords: basketball; special exercises; immediate training effect; physiological changes